Problems faced by principals in the Al Mafraq Directorate in the process of collecting، storing and retrieving information and the importance of providing them with their own database system - Al-Amoush, Alia Muhsen (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the problems faced by the principals in Mafraq in the process of collecting data، processing and refer to it from their point of view in terms of obstacles and challenges، and to identify the impact of both sex and educational qualification and area of specialization and to related experience.The study used the descriptive survey method، which was a questionnaire of 15 paragraphs that were distributed to 110 principals out of 160 in Al Mafraq.The results showed that the degree of use of files and paper documents at an average of 4.4 was at a high level and there was no differences in the statistical significance of variables such as sex or experience.The results of the study showed that the current system using "paper" is a major burden in the process of retrieving، archiving and updating information، and that the current e-learning system does not serve them as required. The current e-learning system obtained a low average of 2 degrees، the internet also has a low average of 2 grades as well. From this point of view, it is necessary to provide an effective system for storing and retrieving information that facilitates administrative operations on school administrators.In light of the results، the study recommended that: Create a system that serves the process of data collection، archiving and processing and to train principals and their assistants on how to use such a system to meet their needs، Encourage principals to use technology effectively because of its role in saving time، effort and ease of dealing and Providing the Internet for its role in obtaining and disseminating information.
Keywords: Data; Information; Data and Data Preservation; Databases and Problems